Roosevelt : the party leader, 1932-1945 - Savage, Sean J., 1964- (The University Press of Kentucky, 2015)
FDR -- the wily political opportunist glowing with charismatic charm, a leader venerated and hated with equal vigor -- such is one common notion of a president elected to an unprecedented four terms. But in this first comprehensive study of Roosevelt's leadership of the Democratic party, Sean Savage reveals a different man. He contends that, far from being a mere opportunist, Roosevelt brought to the party a conscious agenda, a longterm strategy of creating a liberal Democracy that would be an enduring majority force in American politics. The roots of Roosevelt's plan for the party ran back to.
Keywords: Roosevelt, Franklin D. -- (Franklin Delano), -- 1882-1945.; Roosevelt, Franklin D. -- (Franklin Delano), -- 1882-1945; Political leadership -- United States -- History -- 20th century.; United States -- Politics and government -- 1933-1945.; États-Unis -- Politique et gouvernement -- 1933-1945.; HISTORY -- United States -- State & Local -- General.; POLITICAL SCIENCE -- Political Process -- Political Parties.; Political leadership; Politics and government; United States; 1900-1999; History